2019
DOI: 10.3847/1538-4357/ab2466
|View full text |Cite
|
Sign up to set email alerts
|

The Observational Evidence for the Internal Excitation of Sunspot Oscillations Inferred from the Fe i 5435 Å Line

Abstract: The umbral oscillations of velocity are commonly observed in the chromosphere of a sunspot. Their sources are considered to be either the external p-mode driving or the internal excitation by magnetoconvection. Even though the possibility of the p-mode driving has been often considered, the internal excitation has been rarely investigated. We report the identification of the oscillation patterns that may be closely related to the events of internal excitation from the observations of velocity oscillations in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…In other words, the three-minute oscillation can be regarded as the upwardly propagating slow magnetoacoustic waves (e.g., Su et al 2016;Chae et al 2019;Cho & Chae 2020;Feng et al 2020b). Finally, Chae et al (2017) found that the threeminute oscillation in the light bridge or umbral dots of a sunspot originates from the photosphere (see aslo Cho et al 2019), which is consistent with our results and further suggests that the CYRA data is reliable.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In other words, the three-minute oscillation can be regarded as the upwardly propagating slow magnetoacoustic waves (e.g., Su et al 2016;Chae et al 2019;Cho & Chae 2020;Feng et al 2020b). Finally, Chae et al (2017) found that the threeminute oscillation in the light bridge or umbral dots of a sunspot originates from the photosphere (see aslo Cho et al 2019), which is consistent with our results and further suggests that the CYRA data is reliable.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…They are thought to be resonant modes of sunspot oscillations, with cavities that may be located at sunspot umbrae in the solar layers of sub-photospheres (Scheuer & Thomas 1981;Thomas 1984Thomas , 1985 or chromospheres (Uexkuell et al 1983;Gurman 1987;Khomenko & Collados 2015). The typical three-minute oscillation above the sunspot can be simultaneously detected from the photosphere through the chromosphere and transition region to the corona, supporting the interpretation of propagating waves at sunspots (De Moortel et al 2002;O'Shea et al 2002;Brynildsen et al 2004;Su et al 2016;Chae et al 2019), for instance trans-sunspot waves (Tziotziou et al 2006) or slow magnetoacoustic waves (Bloomfield et al 2007;Krishna Prasad et al 2015;Wang et al 2018;Cho et al 2019;Cho & Chae 2020).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Recent observations (Chae et al 2017;Cho et al 2019;Kang et al 2019) rather support the notion that the sources of excitation are located below the atmosphere, as has commonly been modeled by the piston motion at the bottom of the atmosphere in previous theoretical studies (e.g., Fleck & Schmitz 1991;Kalkofen et al 1994;Sutmann & Ulmschneider 1995). These studies found that regardless of the specific form of the piston driving, the oscillations with a frequency close to the cutoff prevail in high altitudes of the atmosphere.…”
Section: Introductionmentioning
confidence: 72%